2009
DOI: 10.1002/ptr.2719
|View full text |Cite
|
Sign up to set email alerts
|

Protective action of aqueous black tea (Camellia sinensis) extract (BTE) against ovariectomy‐induced oxidative stress of mononuclear cells and its associated progression of bone loss

Abstract: The protective action of aqueous black tea extract (BTE) against ovariectomy-induced oxidative stress of mononuclear cells and its associated progression of bone loss was demonstrated in this study. Eighteen female adult 6-month-old Wistar albino rats were divided into three groups: sham-control (A), bilaterally ovariectomized (B) and bilaterally ovariectomized + BTE supplemented (C). Studies included the measurement of oxidative (nitric oxide, lipid peroxidation) and antioxidative (superoxide dismutase, catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 58 publications
(66 reference statements)
1
16
0
Order By: Relevance
“…Some reports have demonstrated that osteoclast differentiation is stimulated by oxidative stress [29]. These data indicate that oxidative stress plays a crucial role in osteoclast differentiation.…”
Section: Resultsmentioning
confidence: 67%
“…Some reports have demonstrated that osteoclast differentiation is stimulated by oxidative stress [29]. These data indicate that oxidative stress plays a crucial role in osteoclast differentiation.…”
Section: Resultsmentioning
confidence: 67%
“…Moderate consumption of tea, which contains flavonoids closely related to soy isoflavones, has been reported to be associated with higher BMD in men and women [26, 27] and lower rates of fracture [32, 33]. Results of series of studies from our laboratory with aqueous black tea extract [34–36] further support the idea that phytocompounds have efficacy in preventing bone loss. This study aimed to examine the protective role of black tea extract (BTE) against nonalcoholic steatohepatitis- (NASH-) induced skeletal dysfunction.…”
Section: Introductionmentioning
confidence: 67%
“…Oxidative stress is regarded as a pivotal physiopathological process in the age-related bone loss [40]. Das AS et al showed that the black tea extract would protect the mononuclear cells from the oxidative stress and thus slowed the progression of bone loss [41]. Apart from the polyphenol, the other contents in tea, such as fluorine and caffeine, also play important roles in the bone health [37].…”
Section: Discussionmentioning
confidence: 99%